Research in leadership effects on public service effectiveness: strengths, weaknesses and future perspectives - Andersen, Lotte Bøgh; Andersen, Simon Calmar; Pallesen, Thomas (Politica, 2016)
Research in public management and public leadership has intensified internationally and in Denmark. The article provides an overview of the impact of public management and leadership on outcomes for citizens. We focus on transformational leadership, which is one of the most prominent leadership approaches, the major strands in the formal structure-oriented management approach and finally the non-leader-oriented distributed and collaborative leadership literature. In the conclusion, we outline promising avenues for future management and leadership research in order to obtain more valid causal claims and more solid knowledge of the impact of the context of the studies.